(untitled) (Research, Society and Development, 2023)
Syphilis is a Sexually Transmitted Infection (STI), caused by Treponema pallidum, which is transmitted through sexual contact, as well as vertically, during pregnancy, from mother to fetus. The objective of this work is to identify, in the scientific literature, the main risk factors for the transmission of syphilis during pregnancy. This is an integrative literature review, for which the Virtual Health Library (VHL) was used for search, through the Descriptors in Health Sciences (DeCS): "Pregnancy", "STI" and "Syphilis". 401 articles were found, from which, after applying the inclusion and exclusion criteria, 73 studies were extracted, of which 12 composed the articles to support this research. The results indicate that the women most susceptible to syphilis infection are those in a more vulnerable socioeconomic situation, who do not receive adequate prenatal care and treatment. Untreated partners or unstable marital situations also increase the risk for infection and/or transmission to the fetus. With that, since syphilis is a public health problem, it becomes important the participation of primary care in mapping pregnant women in vulnerable situations, as well as in the distribution of condoms and the availability of rapid tests so that there is a diagnosis and early intervention. In addition to health education actions for a better awareness of populations at risk.